Anti-stripping roll materials and heat treatment process for high-speed wire pre-finishing mill

By optimizing the chemical composition and heat treatment process of the roll material, the problem of insufficient wear resistance and peeling resistance of the roll material in the high-line pre-finishing mill group is solved, and the efficient use of the roll and the production efficiency of the roll is achieved.

CN118639093BActive Publication Date: 2024-12-31BAOMEITE (SHANGHAI) INTELLIGENT ENG CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411126277.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-31
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The wear resistance and peeling resistance of the roll materials of the existing high-line pre-finishing mills are insufficient, resulting in a short service life of a single-time machine, affecting production efficiency, and the existing heat treatment process is complex and the production cycle is long.

Method used

Using rolling materials containing elements such as C, Si, Mn, Cr, Ni, Mo, V, W, Nb, etc., control carbide and bainite by optimizing chemical composition and heat treatment processes, including annealing, quenching and tempering steps. Form the hardness and toughness of the roll.

Benefits of technology

It significantly improves the wear resistance and peeling resistance of the roll, extends the service life of a single machine, improves production efficiency, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118639093B_ABST
    Figure CN118639093B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of roller casting technology, and more specifically to an anti-stripping roller material and a heat treatment process for a high-speed wire pre-finishing mill. The chemical components of the anti-stripping roller material for a high-speed wire pre-finishing mill include: C, Si, Mn, Cr, Ni, Mo, V, W, Nb, Fe and unavoidable impurities; the heat treatment process of the roller material includes annealing and quenching and tempering, wherein the quenching and tempering steps include: a first heating and heat preservation, a second heating and heat preservation, a third heating and heat preservation, spray quenching and high-temperature tempering. The present invention adopts a new material and a high-performance roller material prepared by a new material and a heat treatment process thereof, which solves the problems of short service life and frequent spalling of raw material rollers, improves production efficiency, reduces production costs, and has a good prospect for promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of roll casting, and more specifically to an anti-stripping roll material and a heat treatment process for a high-speed wire pre-finishing mill. Background Art

[0002] High-speed wire rod mills have the characteristics of high-speed rolling, high quality, and high efficiency, which provide guarantee conditions for high product output and a wide range of product specifications. In recent years, the wire rod production line has adopted short stress wire mills, taking the development path of "high speed, no torsion, and no tension", and developing headless rolling and low-temperature rolling technologies; due to the more diversified product specifications of wire rod production lines, the increasing demand for small-size products, and the continuous improvement of mechanical properties, this requires the mechanical properties of processing equipment to be continuously improved, and the high-speed wire rod production line realizes low-temperature furnace and low-temperature controlled rolling throughout the line, and the microstructure, yield strength and toughness of the obtained products are improved at the same time.

[0003] At present, the rollers used in the front section of high-speed wire pre-finishing rolling are mainly traditional high-nickel-chromium bainite ductile iron. Recent use shows that its wear resistance, anti-stripping and other anti-accident performance are poor. The roller groove surface is often not wear-resistant, peeling and falling, pits, low single groove rolling volume, and frequent roll changes have become bottlenecks for further increasing production capacity. With the high-speed and high-quality development of rolling mills, the service life of this material roller is low due to the above defects, affecting the production efficiency of the production line. This requires that the anti-stripping and wear resistance of the working layer of the pre-finishing mill rolls be greatly improved, while the matrix maintains good strength and toughness.

[0004] Prior art CN91107234.9 discloses vanadium-titanium infinitely cold-hardened ductile iron rolls and a casting method. The chemical composition of the rolls does not contain precious alloy elements such as Ni, Cr, Mo, and Cu. During casting, a mixed spheroidizer composed of rare earth magnesium and iron-magnesium mechanism spheroidizers is used. The rolls produced have low cost, high hardness, good wear resistance, and high strength. However, although the absence of precious alloy elements such as Ni, Cr, Mo, and Cu can reduce costs, it will have certain negative effects on the mechanical properties, excess steel, and wear resistance of the rolls; Prior art CN201410085918 discloses a centrifugally cast method for manufacturing free-cutting high-speed steel rolls. The processing process discloses degradation, quenching and tempering processes, heat treatment processes, etc. However, its heat treatment process is complicated, the heating rate is slow, and the production cycle is long, which affects the scope of application of the process.

[0005] The material of the rough rolling stand rolls of wire rod and section steel rolling mills is generally pearlite ductile iron. During use, there are phenomena such as deep groove cracks, large amount of steel passed in a single time, large amount of turning and large hardness difference. Summary of the invention

[0006] In order to solve the above technical problems, the first aspect of the present invention provides an anti-stripping roll material for a high-speed wire pre-finishing mill, the chemical components of the roll material including: C, Si, Mn, Cr, Ni, Mo, V, W, Nb, Fe and unavoidable impurities.

[0007] Preferably, the mass percentages of V, Mo and W satisfy: V+Mo+W / 2=1.9-4.5%.

[0008] Further preferably, the chemical composition of the rolling mill material includes, by mass percentage, 2.6-3.6% C, 1.3-2.0% Si, 0.5-0.8% Mn, 1.5-3.0% Cr, 1.0-2.5% Ni, 0.2-0.8% Mo, 1.5-3.2% V, 0.5-1.0% W, 0.12-0.25% Nb, and the remainder of Fe and unavoidable impurities.

[0009] The elements in the roller of the present invention play the following roles in the roller:

[0010] C (Carbon): C is the most basic element in the roll material alloy. Its content determines the amount of carbides, M 7 C 3 The relative amount of type carbides and total carbides, hardness, toughness and hardenability of the material, etc., the relevant test results show that the C content of the roll in the present invention is preferably controlled at 2.6-3.6wt%.

[0011] Si (silicon): Silicon can induce bainite nucleation in the alloy matrix of the roll material and increase its nucleation rate. This is because Si can refine the eutectic group, increase the austenitization temperature, increase the supercooling degree ΔT of the austenite transformation, and the small nucleus embryo produced in the austenite can be used as the bainite core or the martensite core; in the present invention, according to the different dynamics of bainite and martensite nucleation, the design of the heat treatment process is improved to control the content of bainite and martensite. The test results show that Si can induce bainite phase transformation, refine the bainite structure, and improve the hardness and toughness. On the other hand, silicon is an element that strongly promotes graphitization and inhibits the precipitation of carbides. The increase in the amount of silicon makes the ductile iron fully inoculated, and a large number of fine and round graphite is obtained, that is, the eutectic group is refined and the bainite structure is also refined. Therefore, it is appropriate to control the Si content to 1.3-2.0wt%.

[0012] Mn (manganese): When the amount of Si remains unchanged, the appropriate reduction of Mn content can improve the comprehensive mechanical properties of bainite. This is mainly because Mn is a positive segregation element, which will reduce the austenitizing temperature, increase the carbon content in austenite, reduce the activity of carbon, stabilize austenite, and drag the transformation of bainite; while silicon is a negative segregation element, which can increase the austenitizing temperature, increase the activity of carbon, make the bainite transformation complete, and improve the performance. The research results show that after adding Mn, the matrix structure is a fine needle-shaped bainite structure, but with the increase of Mn content, the segregation of Mn in the structure is more serious, the amount of martensite at the grain boundary increases, and the carbide is distributed along the grain boundary, and the amount increases, which will lead to a decrease in toughness. Therefore, the amount of Mn added should be controlled below 0.8wt%, and 0.5-0.8wt% is appropriate in the present invention.

[0013] Cr (chromium): Cr is the most important element in the roll material alloy. 7 C 3 The higher the ratio of type carbides, the better the hardenability. The Cr content needs to be controlled to obtain M in the matrix. 7 C 3 Type carbide; experimental research shows that Cr content is greater than 1.5wt% 7 C 3 It exists in the form of carbides; however, as the Cr content increases, the eutectic point shifts to the left. At this time, it is necessary to comprehensively consider the C content and the Cr content so that the Cr element exists in the form of carbides and less exists in the form of solid solution in the matrix. This is because due to the particularity of wire rods, the rolled high-alloy wire often contains a large amount of Cr. When the Cr content dissolved in the roll matrix is ​​too high, steel sticking often occurs. A large number of experiments have shown that when the Cr content in the roll exceeds 3.0wt%, steel sticking will occur. Therefore, the mass percentage of Cr in the present invention is controlled to be: 1.5wt% <Cr<3.0wt%。

[0014] Ni (nickel): Nickel can refine the matrix and enhance the hardening performance of steel. Tests show that adding nickel to the roll matrix has a significant effect on improving the plasticity, toughness and thermal strength of steel. However, considering that nickel is a rare element, its addition is only controlled between 0.8-1.5%; when the mass content of Ni is <0.8%, the room temperature plasticity, toughness and thermal strength of the roll do not increase significantly; when the Ni content is between 0.8-1.5%, its room temperature plasticity, toughness and thermal strength increase with the increase of Ni content; when the mass content of Ni is >1.5%, the increase of room temperature plasticity, toughness and thermal strength does not match the increase in cost, that is, the cost performance is not high.

[0015] V (vanadium): Within the research scope of the present invention, as the amount of V added increases, the bainite structure is significantly refined, the hardness and bainite transformation of bainite ductile iron increase, while the microhardness of austenite and bainite does not change much. Experimental studies have shown that the optimal range of V content is 1.5-3.2wt%.

[0016] The mechanism of V in refining bainite structure can be attributed to two aspects. First, V is one of the elements that strengthen ferrite and austenite. It dissolves into austenite to form a solid solution, reduces the diffusion rate of carbon, and also needs time to diffuse, thereby delaying the transformation of austenite and prolonging the gestation period of bainite transformation. Under the continuous cooling conditions of this experiment, this means that the bainite transformation will be carried out at a lower temperature. The increase in transformation undercooling will bring greater driving force for bainite nucleation. Secondly, during the austenitization process, the VC (vanadium carbon) particles formed during solidification have a "pinning" effect, hindering the movement of grain boundaries and grain growth, refining the austenite grains, and thus providing more favorable nucleation sites for bainite. Due to the above two effects, the bainite core increases significantly, the bainite structure is refined, and the amount of bainite transformation is increased.

[0017] Mo (molybdenum) and W (tungsten): In the technical solution described in the present invention, Mo is a strong carbide-forming element, which improves the stability of austenite and the hardenability of the roll matrix, and prevents the second type of temper brittleness. 6 C-type carbide improves the stability of MC-type carbide and the tempering resistance of the matrix, and inhibits the generation of thermal cracks; therefore, in the technical solution of the present invention, the mass percentage of Mo needs to be controlled between 0.2-0.8%, and the mass percentage of W needs to be controlled between 0.5-1.0%; and (V+Mo+W / 2)=1.9-4.5wt% needs to be satisfied;

[0018] Nb (niobium): The role of the Nb element in the present invention is that it has a strong affinity with carbon, nitrogen and oxygen, and can form extremely stable compounds, which play a role in refining grains, increasing grain coarsening temperature, hardenability and tempering stability; in addition, Nb, as a hard element, can improve the wear resistance of the thickened mold; therefore, in the technical solution of the present invention, the mass percentage of the Nb element is controlled to be: 0.12-0.25wt%.

[0019] The second invention of the present invention provides a heat treatment process for the anti-stripping roll material of a high-speed wire pre-finishing mill group, comprising the following steps: annealing and quenching and tempering.

[0020] Preferably, the annealing step comprises: when the cast roll material is cooled to a temperature of 930-950°C, a furnace-insulated annealing treatment is performed for 3-4 hours, and then heating is stopped, the roll material is slowly cooled to 600°C in the furnace, removed from the furnace, and air-cooled to room temperature.

[0021] Preferably, the quenching and tempering step comprises:

[0022] S1, first heating and insulation;

[0023] S2, second heating and heat preservation;

[0024] S3, third heating and heat preservation;

[0025] S4, spray quenching;

[0026] S5. High temperature tempering.

[0027] Preferably, the first heating and heat preservation comprises: heating the roll material treated in the annealing step at a heating rate of 180-200°C / h, and performing uniform temperature preservation at 700°C for 10-12 minutes.

[0028] Preferably, the second heating and heat preservation comprises: on the basis of step S1, continuing to heat at a heating rate of 180-200°C / h, and at 900°C, performing uniform temperature preservation for 10-12 minutes.

[0029] Preferably, the third heating and heat preservation comprises: on the basis of step S2, heating to 980-1100° C., heat preservation for 30-40 minutes, and quenching after taking out of the furnace.

[0030] Preferably, the spray quenching includes: on the basis of step S3, by testing the spray flow rate of the spray cooling device, the cooling rate of the roller body of the roll material is 2-4°C / s; after 245-550s, blowing air to the roller body, the highest temperature return during the blowing stage is 340-350°C, until the roller temperature is 150°C-170°C, stop blowing and air cool until the roller body temperature stabilizes at 150°C-170°C.

[0031] Preferably, the high temperature tempering step comprises: preheating the tempering furnace to 100-150°C; then, based on step S4, heating the roll material at a heating rate of 180-200°C / h, tempering and keeping warm at 480-600°C for 90-120min; cooling to 150°C with the furnace, and air cooling to room temperature after being taken out of the furnace; and repeating the high temperature tempering process 2-3 times.

[0032] In the processing steps of the present invention, multiple equalization and heat preservation are required during the heating process. This is because, when the heating rate is fast and the quenching temperature is high, short-term equalization and heat preservation can make the rollers heated evenly; therefore, in the S1 and S2 steps of the technical solution of the present invention, two equalization and heat preservation times of 10-12 minutes are carried out at 700°C and 900°C.

[0033] In the treatment process S3 and S4 of the present invention, high temperature quenching is performed at 980-1100°C, the spray flow rate is reasonably controlled, the cooling rate of the roller body is controlled to be 2-4°C / s, and the microstructure is controlled to be bainite, a small amount of martensite, residual iron and carbide. The spray cooling time is controlled to be 245-550s, and the thickness of the working layer is properly controlled to be 35-40mm.

[0034] The high temperature quenching at 980-1100℃ is because the alloy composition in the roll material is optimized in the present invention, and the high melting point carbides increase. MC is the carbide of V, which precipitates during the eutectic transformation or from austenite, and its starting solid solution temperature is 1000-1150℃. VC particles are fine and evenly distributed. 6 C is the carbide of W and Mo, which is dissolved in austenite at 1050-1300℃. 6 C is quite stable and not easy to aggregate and grow, which can increase the hardness and wear resistance of the mold. 7 C 3 It is a carbide of Cr, which is a primary eutectic carbide or a secondary carbide precipitated from austenite. It can dissolve elements such as W, Mo, and V to increase wear resistance and reduce friction coefficient. 7 C 3 Dissolves into austenite at 950-1150℃; M 23 C 6 It is another Cr carbide, which begins to dissolve at a temperature of 1000-1020°C, and requires a temperature of 1150-1200°C to completely dissolve in austenite. Therefore, a higher quenching temperature of 980-1100°C must be used to fully dissolve the carbide into the matrix.

[0035] In the high-temperature tempering step of the processing process S5 of the present invention, the quenching process adopts high-temperature quenching. Experiments show that by adopting high-temperature quenching and combining with a higher tempering temperature of 480-600℃, the thermal fatigue resistance of the iron roll of the rolling mill is increased. During the service process, the initiation time of thermal cracks on the roll surface is delayed, and the crack propagation rate is also reduced; this is because the austenitization temperature is increased, more carbides are melted in the matrix, the matrix alloy elements and carbon solid solubility increase, the matrix is ​​effectively strengthened, and the strength and toughness are improved; in addition, the higher tempering temperature improves the tempering resistance of the roll body, and the thermal cycle stability is also improved, which effectively reduces the failure of the roll surface peeling during the rolling process. The tempering holding time is controlled within 120min to ensure that the hardness of the tension-reducing roll meets the requirements while having higher strength and toughness.

[0036] Beneficial Effects

[0037] (I) Compared with the traditional pearlite roll, the roll material of the present invention has a 1.5 times higher steel passing capacity, no peeling or micro-cracks on the roll surface, and a 20-30% lower grinding amount. The overall cost performance is more than doubled.

[0038] (ii) The new material of the high-strength pre-finishing mill roll and its heat treatment process newly designed in the present invention increases the strength and toughness of the roll matrix by designing the material composition to meet the low-temperature rolling requirements of high-strength steels such as spring steel and cold heading steel.

[0039] (III) At the same time, the present invention adopts a matching heat treatment process, which comprehensively improves the room temperature and high temperature mechanical properties of the new rolling mill material, especially the high temperature toughness, oxidation resistance and thermal crack resistance are greatly improved, solving the problems of short service life and frequent peeling of the new rolling mill material on a single machine, improving production efficiency and reducing production costs; at the same time, the microstructure of the rolling mill treated by the heat treatment step is improved from the original pearlite to bainite, further improving the accident resistance of the rolling mill material matrix.

[0040] (IV) The room temperature hardness of the high-speed wire pre-finishing mill roll developed by the present invention is 75-80HSD, and the tensile strength is 600-650MPa; at 600°C, the hardness is 50-55HSD, and the tensile strength is 500-550MPa, with excellent performance.

[0041] (V) The present invention develops a bainite ductile iron roll specially used for rough rolling, strengthens and refines the matrix structure by adding special alloy elements, designs and optimizes its chemical composition and heat treatment process, and develops bainite + martensite roll materials without significantly increasing the cost, so that the roll has a higher matrix strength, improves the accident resistance, wear resistance and single-time service life of the rolls of the roughing and medium rolling mills. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the crystal phase diagram of the roller in Example 1 after the heat treatment step (scale: 20 μm). DETAILED DESCRIPTION

[0043] Example 1

[0044] The first aspect of this example provides an anti-stripping roll material for a high-speed wire pre-finishing mill, wherein the chemical element components in the roll material are as follows in terms of mass percentage: 2.6% C, 1.3% Si, 0.5% Mn, 1.5% Cr, 1.0% Ni, 0.2% Mo, 1.5% V, 0.5% W, 0.12% Nb, and the remainder of Fe and unavoidable impurities.

[0045] The second aspect of this example provides a process for heat treatment of anti-stripping roll materials of a high-speed wire pre-finishing mill, which specifically comprises the following steps: annealing and quenching and tempering.

[0046] The annealing step includes: when the cast roll material is cooled to a temperature of 940°C, a 4-hour furnace-insulated annealing treatment is performed, and then heating is stopped, the roll material is slowly cooled to 600°C in the furnace, and then air-cooled to room temperature 25°C after being taken out of the furnace.

[0047] The quenching and tempering steps include:

[0048] S1. First heating and heat preservation: heating the roll material treated in the annealing step at a heating rate of 200°C / h, and heat preservation for 10 minutes at 700°C;

[0049] S2, second heating and heat preservation: on the basis of step S1, continue heating at a heating rate of 200°C / h, and when the temperature reaches 900°C, perform uniform temperature preservation for 10 minutes;

[0050] S3, third heating and heat preservation: based on step S2, heating to 1100°C, heat preservation for 40 minutes, and quenching;

[0051] S4, spray quenching: on the basis of step S3, the cooling rate of the roll body of the roll material is 2°C / s by testing the spray flow rate of the spray cooling device; blow air to the roll body for 475s, the highest temperature return during the blowing stage is 350°C, until the roll temperature reaches 150°C, stop blowing and air cool until the roll body temperature stabilizes at 150°C;

[0052] S5, high temperature tempering: preheat the tempering furnace to 150°C, then based on step S4, heat the roll material to 600°C at a heating rate of 180°C / h, and temper and keep warm for 120 minutes; cool to 150°C with the furnace, and air cool to room temperature 25°C after being taken out of the furnace.

[0053] The high temperature tempering step was repeated 3 times.

[0054] Example 1 The crystal phase diagram of the material after the roller is subjected to the heat treatment step is as follows Figure 1 shown.

[0055] Embodiment 2-5

[0056] The specific implementation methods of Examples 2-5 are the same as those of Example 1, except that the mass percentages of the chemical element components in the roller material are different, see Table 1 for details.

[0057] Table 1 Composition of Examples 1-5 (wt%)

[0058]

[0059] Comparative Example 1

[0060] The first aspect of this example provides a rolling mill material, in which the chemical element components in the rolling mill material are calculated by mass percentage as follows: 2.8% C, 0.7% Si, 0.6% Mn, 1.6% Cr, 1.0% Ni, 0.2% Mo, 1.5% V, and the remainder Fe and unavoidable impurities.

[0061] The second aspect of this example provides a process for heat treatment of rolling mill materials, which specifically comprises the following steps: softening and annealing the cast rolling mill at 1000°C, then quenching at 960°C, tempering at 500°C, and cooling down to room temperature 25°C after being taken out of the furnace.

[0062] Performance Testing

[0063] 1. Mechanical properties test

[0064] Test objects: Mechanical properties at room temperature (25°C) and high temperature mechanical properties (test temperature: 600°C) of the roller materials of Examples 1-5, where the reference for mechanical properties at room temperature is GB / T228.1-2021; the reference for mechanical properties at high temperature is GB / T228.2-2015. The test results are detailed in Table 2.

[0065] Table 2 Mechanical properties test results

[0066]

[0067] As shown in Table 1 and Table 2, the tensile strength R of the rolling mill rolls in the new materials in Examples 1-5 at room temperature is m 600-650MPa, impact energy A KU2 The tensile strength is 3.6-5.0J, and the hardness HSD is 52-55; at 600℃, the tensile strength is 510-548MPa, and the hardness HSD is 51-55.

[0068] 2. Mechanical properties test

[0069] Test objects: the rollers described in Example 1 and Comparative Example 1. The test results are detailed in Table 3.

[0070] Table 3 Comparison of average rolling amount per machine

[0071]

[0072] The test method or test standard for the average rolling amount of a single machine: For conventional rolls, based on usage experience, there are rolling regulations that specify a fixed rolling tonnage, and the rolls are replaced when the rolling tonnage is reached.

[0073] For the new material rolls developed in the present invention, after the rolls are put on the machine, during the short downtime for switching specifications, the staff will go to the rolling mill to observe the surface condition of the rolls. If no defects such as microcracks and peeling are observed, they can continue to be used until roll surface defects appear and the rolls are taken off the machine. At this time, the rolling tonnage is counted, which is the rolling tonnage of the new material rolls in this single machine operation.

[0074] In order to solve the problems that the roller surface of the existing rollers is easy to peel off and the single machine time cannot meet the production line requirements, the present invention adopts new materials and heat treatment processes to prepare new high-performance roller materials with excellent strength, toughness, wear resistance and thermal cracking resistance, solves the problems of short service life and frequent peeling of raw material rollers, improves production efficiency, reduces production costs, and has good prospects for promotion and application.

Claims

1. A high-speed wire pre-finishing mill unit anti-stripping roll material, characterized in that: The chemical composition of the rolling roller material includes, by mass percentage, 2.6-3.6% C, 1.3-2.0% Si, 0.5-0.8% Mn, 1.5-3.0% Cr, 1.0-2.5% Ni, 0.2-0.8% Mo, 1.5-3.2% V, 0.5-1.0% W, 0.12-0.25% Nb, the remainder Fe and unavoidable impurities; the mass percentage of V, Mo and W satisfies: V+Mo+W / 2=1.9-4.5%.

2. A heat treatment process for the anti-stripping roll material of the high-speed wire pre-finishing mill according to claim 1, characterized in that: The heat treatment process of the roll material includes: an annealing step and a quenching and tempering step; The quenching and tempering steps include: S1, first heating and insulation; S2, second heating and heat preservation; S3, third heating and heat preservation; S4, spray quenching; S5. High temperature tempering.

3. The heat treatment process for the anti-stripping roll material of the high-speed wire pre-finishing mill according to claim 2 is characterized in that: The annealing step comprises: When the cast roll material is cooled to a temperature of 930-950°C, it is subjected to a 3-4h furnace-insulated annealing treatment, and then the heating is stopped, the roll material is slowly cooled to 600°C in the furnace, and then air-cooled to room temperature after being taken out of the furnace.

4. The heat treatment process for the anti-stripping roll material of the high-speed wire pre-finishing mill according to claim 2 is characterized in that: The first heating and heat preservation step comprises: The roll material treated in the annealing step is heated at a heating rate of 180-200°C / h, and is kept at 700°C for 10-12 minutes.

5. The heat treatment process for the anti-stripping roll material of the high-speed wire pre-finishing mill according to claim 2 is characterized in that: The second heating and heat preservation step comprises: On the basis of step S1, the roller material continues to heat up at a heating rate of 180-200°C / h, and at 900°C, is kept evenly heated for 10-12 minutes.

6. The heat treatment process for the anti-stripping roll material of the high-speed wire pre-finishing mill according to claim 2 is characterized in that: The third heating and heat preservation step comprises: On the basis of step S2, the roll material is heated to 980-1100°C, kept at this temperature for 30-40 minutes, and then taken out of the furnace for quenching.

7. The heat treatment process for the anti-stripping roll material of the high-speed wire pre-finishing mill according to claim 2 is characterized in that: The spray quenching comprises: On the basis of step S3, the cooling rate of the roller body of the roll material is 2-4°C / s through the spray flow of the spray cooling device; after 245-550s, air is blown to the roller body, and the maximum temperature return during the blowing stage is 340-350°C, until the roller temperature is 150°C-170°C, stop blowing and air cool until the roller body temperature stabilizes at 150°C-170°C.

8. The heat treatment process for the anti-stripping roll material of the high-speed wire pre-finishing mill according to claim 2 is characterized in that: The high temperature tempering step in step S5 includes: The tempering furnace is preheated to 100-150°C, and then, based on step S4, the roll material is heated in the tempering furnace at a heating rate of 180-200°C / h to 480-600°C, and tempered for 90-120 minutes; cooled to 150°C with the furnace, and air-cooled to room temperature after being taken out of the furnace; the high temperature tempering step is repeated 2-3 times.

Citation Information

Patent Citations

  • Process for manufacturing centrifugally-cast easy-cutting high-speed steel roll

    CN103805902A

  • Roller made of infinitely chilled vanadium and titanium contained nodular cast iron and its casting process

    CN1068149A

  • cold work steel WITH HIGH WEAR RESISTANCE

    AT411534B

  • Wear-resistant high holding precision rolling rear working roller and production method thereof

    CN101956124A

  • Centrifugal composite high-nickel-niobium wear-resisting cast iron roll and casting method thereof

    CN103074539A